THE CONCEPT OF A PRODUCT AND ITS PLACE IN THE MARKETING SYSTEM. - Hayitov Vazirbek; Hayitov Marvarbek; Aruslanov Saidamin (Scholar Express Journal, 2024)
A product is a product created to satisfy a need and offered in the market for the purpose of attracting attention, purchase, use or consumption. These can be various physical objects, services, persons, places, organizations and ideas. In the marketing system, it is considered as a set of useful features that more fully satisfy the needs of the target group of consumers, the presence of demand for the product in the market and the determination of the date of sale (together with a certain price).
Keywords: Product; physical; objects